Factors influencing quality of life of nondemented elderly nursing homes residents [Huzurevi̇nde kalan demansi olmayan yaşlilarda yaşam kali̇tesi̇ni̇etki̇leyen faktörler] - (:unkn) unknown (My University, 2006)
Background and Aim: Increase in admission to nursing homes is expected while elderly population is increasing. We aimed to determine which factors may influence quality of life of elderly nursing home residents. Materials and Method: Sixty nine eldery residing at 5 different nursing homes in the Anatolian region of Istanbul were admitted to the study. Results: Correlations between WHOQOL - BREF subscale scores and Katz's Basic and Lawton's Instrumental Activities of Daily Living scale scores, Yesevage's Geriatric Depression Scale score and various sociodemographic characteristics were investigated. Basic and instrumental activities of daily living, depression symptoms, numbers of chronic illnesses and medications, socioeconomic status, frequency of visits by relatives, relationship with residents and employee, satisfaction with living in a nursing home, feeling of loneliness, activities inside and outside the nursing home were found correlated with different subscales of quality of life scale. Stepwise linear regression analyses determined strongest risk factors for psychological health field of quality of life as depression symptoms, relationship with residents and satisfaction with living in a nursing home, for physical health field as basic and instrumental activities of daily living, number of chronic illnesses and satisfaction with living in a nursing home, for social interest field as number of visits and relationship with residents, for environment field as satisfaction with living in a nursing home, socioeconomic status and relationship with residents. Conclusion: Recognition and improvement in correlating factors may enhance quality of life. Particularly improvement of relationship of residents with each other and questioning satisfaction of residing in a nursing home may enhance quality of life in multiple fields.
Keywords: Elderly; Nursing home; Quality of life; WHOQOL-BREF